2009
DOI: 10.1016/j.gloplacha.2008.03.010
|View full text |Cite
|
Sign up to set email alerts
|

High frequency sea level fluctuations recorded in the Black Sea since the LGM

Abstract: This paper presents a 3D geometric interpretation of very high resolution seismic Chirp profiles acquired on the Romanian shelf during ASSEMBLAGE European Project. The results provide a solid record of the Black Sea Last Glacial Maximum (LGM) water level fluctuations. This pseudo-3D seismic interpretation shows that the Black Sea lacustrine shelf deposits form a significant basinward-prograding wedge system. On top of these prograding sequences is a set of sand dunes that delineates a wave cut-terrace like fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 48 publications
(72 reference statements)
4
49
0
Order By: Relevance
“…At that time, the water level was controlled by regional climate and varied independently from global sea level (Ross et al, 1970). Based on seismic stratigraphy (Ryan et al, 1997;Winguth et al, 2000;Aksu et al, 2002;Lericolais et al, 2009Lericolais et al, , 2010Lericolais et al, , 2011 and reservoir age reconstructions (Soulet et al, 2011a), it is suggested that the water level of the Black Sea 'Lake' oscillated from ca − 150/− 100 m (e.g., during the LGM) to ca. − 35/− 25 m, that corresponds to the depth of the Bosphorus sill.…”
Section: Climate and Water-level Fluctuations In The Black Sea Duringmentioning
confidence: 99%
“…At that time, the water level was controlled by regional climate and varied independently from global sea level (Ross et al, 1970). Based on seismic stratigraphy (Ryan et al, 1997;Winguth et al, 2000;Aksu et al, 2002;Lericolais et al, 2009Lericolais et al, , 2010Lericolais et al, , 2011 and reservoir age reconstructions (Soulet et al, 2011a), it is suggested that the water level of the Black Sea 'Lake' oscillated from ca − 150/− 100 m (e.g., during the LGM) to ca. − 35/− 25 m, that corresponds to the depth of the Bosphorus sill.…”
Section: Climate and Water-level Fluctuations In The Black Sea Duringmentioning
confidence: 99%
“…The initial exposure of the shelf margin triggered instability and failure of the outer shelf and slope, generating gravitational gliding and mass transport of sediments toward the deep-sea part of the basin [Dinu et al, 2005;Ţambrea, 2007]. Rapid sea level changes are also inferred for the Pliocene-Quaternary endemic evolution of the Western Black Sea [Winguth et al, 2000;Lericolais et al, 2009], when sea level drops triggered the transport of important volumes of sediments toward the deep-sea part of the basin. Consequently, thick successions of mass-transport and turbiditic deposits are observed along a number of deep-sea fans in front of modern rivers discharging into the Black Sea [e.g., Popescu et al, 2001].…”
Section: Constraints On the Opening And Inversion Of The Western Blacmentioning
confidence: 99%
“…Both are compatible with the archaeological data discussed in this paper. However, data from Lericolais et al (2009) strengthen the hypothesis of a Black Sea flooding around 7400 bce.…”
Section: Introductionmentioning
confidence: 69%
“…In the case of the Black Sea, the hypothesis of a rapid flooding around w7400 bce is still a controversial topic (Ryan et al, 1997;Görür et al, 2001;Hiscott et al, 2007;Yanko-Hombach, 2007 and review within; Lericolais et al, 2009). Scenarios proposed by Major (2006) and Lericolais et al (2009) rest on imprecise radiocarbon dating related to the hardwater effect discussed by Fontugne et al (2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation